Assessment and Comparison of Agriculture Drought Risk Indexes in the Hemavathi Command Area, Cauvery Basin - Anjana Sinha,; A.S. Ravikumar, (Journal of the Indian Society of Soil Science, 2025)
Identification of drought events is crucial for risk management in agriculture. This aids in the analysis of water resource constraints for the main crops, finger millet and rice, which are farmed in the Nagamangala taluk of the Mandya district of Hemavathi command area. This study’s goal is to analyse drought prone areas using a variety of drought indices including Crop Water Deficit Index (CWDI), Water Scarcity Index (WSI), Water Requirement Satisfaction Index (WRSI) and Seasonal Crop Water Deficiency (SCWD). It has been determined that the initial, development, mid-season and late-season CWDI values for paddy were 19.64, 20.67, 11.78 and 27.56 respectively. The value of WSI were 3.96, 1.47, 1.51 and 1.58 and WRSI were 31.705, 34.163, 40.836 and 40.779 for different growth stages of paddy crops. While for finger millet CWDI values were 0, 0, 26.99 and 0 respectively. The value of WSI were -0.17, -0.02, 0.12 and -0.13 and WRSI are 8.05, 17.75, 32.63 and 24.46 for different growth stages of finger millet. Also, SCWD for paddy and finger millet are 0.184 and -0.188 for the whole growth stage. After comparison, it has been established that there has been moderate drought for paddy while normal to mild drought for finger millet.